Stressors, personality and wellbeing among language teachers. (June 2019) - MacIntyre, Peter D.; Ross, Jessica; Talbot, Kyle; Mercer, Sarah; Gregersen, Tammy; Banga, Claire Ann
Abstract: Teaching foreign/second languages is an inherently stressful occupation, with levels of stress increasing for educators across the globe. Given that language teachers' perceptions of stress and sense of wellbeing are central to their ability to teach well, it is surprising that this topic has received so little research attention to date. This study examines correlations among personality, wellbeing and stress among an international sample of language teachers. As the first part of a larger study, measures of the big five personality traits (extraversion, agreeableness, conscientiousness, emotional stability, and openness), the PERMA wellbeing framework (positive emotion, engagement, relationships, meaning, and accomplishments), and two types of stressors (chronic stressors, and life events/daily hassles) were gathered via eMoodie, a specially designed smartphone app. Results show that both personality and stress are consistently correlated with teacher wellbeing. However, personality and stress were not found to correlate with each other. Results point to the need to better understand both the sources of stress and the positive uplifts experienced by teachers as they contribute to wellbeing. Given the important role(s) played by teachers, it is imperative that research contributes to a better understanding of how language teachers can flourish in their profession.